A Clinical Study on Initial Experience of COVID-19 ARDS in Obstetric Patients at a Tertiary Care Centre in India. (30th March 2021) - Marwah, Sheeba; Kanwar, Reenu; Naghma, Shahida; Dabral, Anjali; Gupta, Nitesh
Abstract : Coronavirus disease 2019 (COVID-19) is caused by a novel coronavirus (severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)) which causes severe viral pneumonia rapidly leading to acute respiratory distress syndrome (ARDS). Pregnant women are considered more vulnerable to severe viral respiratory infections owing to the physiological changes in pregnancy. In COVID-19, patient can present with a variety of symptoms of which dyspnoea is one that is also commonly seen in the late stages of pregnancy. The clinical presentation as well as response to therapy is highly variable, and since no conclusive proven treatment is available yet, prevention and symptomatic treatment remains the mainstay of management. Thus, we report a case series of four SARS-CoV-2-positive obstetric patients who presented with severe ARDS in a tertiary care hospital, posing diagnostic and therapeutic challenges to the clinician, and were managed with a holistic multidisciplinary stepwise approach. Through this, an effort has been made to sensitize the attending obstetrician on diverse presentation of COVID-19 disease and to emphasize the importance of prevention, early pick up, and timely optimal management of pneumonia in pregnant females with COVID-19. The clinical presentation of respiratory illness due to SARS-CoV-2 in pregnancy can be mistaken for exaggerated physiological changes of pregnancy leading to delay in seeking medical care. During the current pandemic, high suspicion for COVID-19 should be kept. If found symptomatic, immediate care should be sought in a designated facility and managed accordingly preferably with a multidisciplinary approach.